Fundamental role of inferior olive connexin 36 in muscle coherence during tremor - Placantonakis, Dimitris G. (National Academy of Sciences, 2004)
Inferior olive (IO) neurons are electrically coupled by cytosolic pores formed by the neuron-specific connexin 36 (Cx36). Electrical coupling in the IO figures prominently in current views about brain control of movement. However, a role for Cx36 in movement has been questioned and not definitively demonstrated. Previous reports have shown that embryonic deletion of the Cx36 gene resulted in almost complete loss of cytosolic and electrical coupling in the IO without an obvious deficit in movement, possibly due to developmental compensations in ionic conductances that can confound the approach of embryonic gene deletion. We used a replication-incompetent lentiviral vector to stably express a dominant-negative Cx36 mutant in the IO of adult rats. We show that interneuronal cytosolic coupling is severely reduced by the mutant Cx36, without effect on neuron morphology or electrical properties. Multisite electromyography revealed that blocking Cx36 in the IO impaired the coherence of muscle firing during harmaline tremor without affecting its rhythm. The data demonstrate that gap junction coupling within the IO mediated by Cx36 adds 10–20 ms of precision to the fine temporal coordination of muscle firing during movement.